PENGARUH KECERDASAN EMOSIONAL, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA TUTOR DI KABUPATEN GOWA - Siti Nursyamsi; Andi Mappatompo (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2018)
This study aims to determine the effect of emotional intelligence on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. This research was conducted in Sombaopu Subdistrict, Gowa Regency with an implementation time of 2 months, namely January to February 2018 with a sample of 42 people. The type of data used in this research is quantitative data.The Emotional Intelligence variable (X1) has a positive and significant effect on the performance of PAUD SPAS tutors in Sombaopu District, Gowa Regency. The results of the hypothesis test show that the t significance value of the emotional intelligence variable is smaller than 0.05 so that Ho is rejected and Ha is accepted, which means that the hypothesis which states